A rapid method for interfacial tension calculation between rock plug and crude oil based on contact angles, application for EOR. (18th August 2018) - Ramírez-González, Patsy V.; Zavala Arriaga, María Mercedes; Escobar-Barrios, Vladimir A.
ABSTRACT: Interfacial tension and contact angle are two specific important parameters to take decisions for enhanced oil recovery, for instance, proper chemicals to use for surface tension reduction, expected wettability of solids, interaction between crude oil and rock. For this purpose, the article presents a method for easy calculation of the solid-liquid interfacial tension based on contact angle measurements applying Neumann's correlation and Young's equation. The main idea stands on the calculation of the rock parameters, like wettability, with known substances and extend these results to crude oils. It was possible, based on the results obtained, to establish a relationship between solid-liquid interfacial tension and contact angle for the crude oil – rock system, which can definitively be used for the calculation of interfacial tension of any other fluid spread out on the same kind of rock. A linear regression was obtained with an accuracy as good as R 2 = 0.9989. Viscosity as a function of contact angle could also be obtained for the studied crude oils in the same kind of rock.